Made in Mexico : Regions, Nation, and the State in the Rise of Mexican Industrialism, 1920s-1940s - Gauss, Susan M., 1968- (Book collections on Project MUSE., 2010)
"Traces conflicts in Mexico over regional authority and labor-employer relations between the state and competing industrialist and labor groups in Guadalajara, Mexico City, Monterrey, and Puebla from the 1920s to the 1950s"--Provided by publisher.